Simulation of Solar Photovoltaic, Biomass Gas Turbine and District Heating Hybrid System - Sami, S; Marin, E (International Journal of Sustainable Energy and Environmental Research, 2017)
This paper presents a simulation model for Biomass-Photovoltaic Hybrid system. The energy conversion equations describing the total power generated by system have been presented. A numerical model based upon the aforementioned conservation equations was developed, coded and results were presented and analyzed. The model is intended to be used as an optimization, design and analysis tool for typical gas turbine Biomass-CHP hybrid systems. The results predicted by the proposed model compared fairly with data under various biomass loading conditions.